DISFUNGSI SEKSUAL PADA WANITA PENDERITA DIABETES MELITUS TIPE 2 - Ratna Saraswati, Made; Sanjaya Funistera, Surya (journal of internal medicine, 2012)
Female Sexual Dysfunction (FSD) has received less attention from doctors, beside very rare complained from patients. This is a contrast situation compare to male with diabetes, for example in general, erectile dysfunction is a common problem reported and decrease patient?s quality of life. A cross sectional study has done, enrolling 97 type 2 diabetes female at outpatient clinic Sanglah Hospital Denpasar. FSD was assessed using FSFI (the female sexual function index) with 19 items of questions. Based on the score of the answer, FSD cathegorized into four categories, including desire disorders, arousal disorder, orgasmic disorder, and sexual pain disorder. In this study, mean age was 58.8 years (SD 8.9), age range between 34 ? 80 years; and mean duration of diabetes was 8.6 years (SD 8.0), range between 0 ? 30 years. Sexual function index of type 2 diabetes female were low, arousal domain was the lowest score: 2.13 or 35.5% of maximum 6 score of this domain. Other domains also have low score under 50%, including desire, lubrication, orgasm, and pain: 41.83%, 42.0%, 39.5%, 48.5%, respectively. Only satisfaction has more than 50%. There was significant association between each domain. Significant and strong negative association were found between all domain and total score with age, followed by duration of diabetes, and number of children. While obesity, glycemic control, lipid profile were not associated with female sexual function index in type 2 diabetes.
Keywords: female sexual dysfunction, type 2 diabetes